2018
DOI: 10.1073/pnas.1813161116
|View full text |Cite
|
Sign up to set email alerts
|

Conotoxin κM-RIIIJ, a tool targeting asymmetric heteromeric K v 1 channels

Abstract: The vast complexity of native heteromeric K+ channels is largely unexplored. Defining the composition and subunit arrangement of individual subunits in native heteromeric K+ channels and establishing their physiological roles is experimentally challenging. Here we systematically explored this “zone of ignorance” in molecular neuroscience. Venom components, such as peptide toxins, appear to have evolved to modulate physiologically relevant targets by discriminating among closely related native ion channel compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…For example, testing of conotoxin κM-RIIIJ over 12 different heterodimers containing Kv1.2 subunits, Cordeiro et al showed that RIIIJ was most potent against Kv1.1/Kv1.2 heterodimers without apparent regard for their arrangement, showing significant discrimination against other heterodimeric constructs including those formed by association of Kv1.2 with Kv1.5 or Kv1.6. Further functional analyses showed that RIIIJ was indeed~100 more potent against hetero-tetramers made of three copies of Kv1.2 α-subunits and one of either Kv1.1 or Kv1.6 in a 3:1 stoichiometry [82]. This detailed functional and biochemical characterization then enabled the use of RIIIJ as a molecular tool for the classification of live large DRG neurons into six discrete functional populations [83].…”
Section: Kv1-active Toxins In Research and Drug Discoverymentioning
confidence: 92%
See 2 more Smart Citations
“…For example, testing of conotoxin κM-RIIIJ over 12 different heterodimers containing Kv1.2 subunits, Cordeiro et al showed that RIIIJ was most potent against Kv1.1/Kv1.2 heterodimers without apparent regard for their arrangement, showing significant discrimination against other heterodimeric constructs including those formed by association of Kv1.2 with Kv1.5 or Kv1.6. Further functional analyses showed that RIIIJ was indeed~100 more potent against hetero-tetramers made of three copies of Kv1.2 α-subunits and one of either Kv1.1 or Kv1.6 in a 3:1 stoichiometry [82]. This detailed functional and biochemical characterization then enabled the use of RIIIJ as a molecular tool for the classification of live large DRG neurons into six discrete functional populations [83].…”
Section: Kv1-active Toxins In Research and Drug Discoverymentioning
confidence: 92%
“…An in-depth evaluation of RIIIJ was performed against heteromeric channels generated by a covalent linkage composed of Kv1.2 and all other Kv1s subunits (except for Kv1.8) at different stoichiometries and arrangements [82]. This work revealed that RIIIJ exquisitely targets asymmetric Kv channels composed of three Kv1.2 subunits and one Kv1.1 or Kv1.6 subunit.…”
Section: κM-riiijmentioning
confidence: 99%
See 1 more Smart Citation
“…After 5 min, a solution of 20 mM K + plus 100 nM cdg14a was again applied to the neurons for 10 s. The cells were allowed to recover for 12 min, and then 20 mM K+ was applied to determine the reversibility of the cdg14a effect. The cells were then incubated for 5 min in a DRG observation solution containing 1 μM of the conopeptide κM-RIIIJ to identify cells expressing Kv1.1 and/or Kv1.2 [ 28 ]. Direct response to κM-RIIIJ, as well as response to 20 mM K+ after κM-RIIIJ incubation, indicating an indirect response, characterizes classes of DRG neurons [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Voltage-sensitive binding/blocking of voltage-gated K-channels [15] Cancer [93], cardioprotection in ischemia [94] κM-RIIIJ Voltage-gated K + channels Subtype selectivity [95,96] Neuronal profiling [5,6,97,98], channel subtype expression profiling [96,99] ω-GVIA Voltage-gated Ca 2+ channels Subtype selective [37,99] Neurotransmission [100][101][102], pain [103], cardiology [55], epilepsy [104], renal function [105], nuclear signaling [106] ω-MVIIC Voltage-gated Ca 2+ channels Inhibits various subtypes broadly [107,108] Epilepsy [109], long-term depression [110], pain [111,112]…”
Section: Research Toolsmentioning
confidence: 99%